2005
DOI: 10.1016/j.bulm.2004.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel moment closure approximations in stochastic epidemics

Abstract: Moment closure approximations are used to provide analytic approximations to nonlinear stochastic models. They often provide insights into model behaviour and help validate simulation results. However, existing closure schemes typically fail in situations where the population distribution is highly skewed or extinctions occur. In this study we address these problems by introducing novel second-and thirdorder moment closure approximations which we apply to the stochastic SI and SIS models. In the case of the SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 29 publications
1
78
0
Order By: Relevance
“…The stochastic logistic model is the stochastic birth-death analogous model of the well-known deterministic Verhulst-Pearl equations (Verhulst, 1838;Pearl and Reed, 1920;Pielou, 1977) and has been extensively used for modeling stochasticity in population biology Kiffe, 2002, 1996;Matis et al, 1998;Krishnarajah et al, 2005). For this continuous-time birth-death Markov process, the conditional probabilities of a unit increase and decrease, respectively, in an "infinitesimal" time interval (t,t + dt] are given by…”
Section: Model Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The stochastic logistic model is the stochastic birth-death analogous model of the well-known deterministic Verhulst-Pearl equations (Verhulst, 1838;Pearl and Reed, 1920;Pielou, 1977) and has been extensively used for modeling stochasticity in population biology Kiffe, 2002, 1996;Matis et al, 1998;Krishnarajah et al, 2005). For this continuous-time birth-death Markov process, the conditional probabilities of a unit increase and decrease, respectively, in an "infinitesimal" time interval (t,t + dt] are given by…”
Section: Model Formulationmentioning
confidence: 99%
“…Continuous-time birth-death Markov processes have been extensively used for modeling stochasticity in population biology Kiffe, 2002, 1996;Matis et al, 1998;Krishnarajah et al, 2005). The time evolution of these processes is typically described by a single equation for a probability function, where time and species populations appear as independent variables, called the Master or Kolmogorov equation (Bailey, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…The ODE of the nth moment of infecteds, derived from the master equation, (see Krishnarajah et al [8]) is given by…”
Section: Moment Closurementioning
confidence: 99%
“…In the cases where the distributions are skewed, the closure method used consisted in using cumulant truncation by setting the fourth cumulant equal to zero. Krishnarajah et al [8] explored the use of mixture distributions, based on a mixture of a point mass at zero representing extinction of the process, and log-normal and beta-binomial distributions to approximate the distribution conditional upon non-extinction. Clancy and Mendy [5] found that: to the quasi-stationary distribution of an SIS model is preferred; (ii) in the supercritical region, a beta-binomial distribution is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…First group operates in terms of stochastic control (Yong, 1999) and (Biagini et al, 2002), second one is based on converting the task (9) to non-random fractional optimal control (Jumarie, 2003). It is also possible to use system of moments equations instead of equation (5) as it was proposed in (Krishnarajaha et al, 2005) and (Lloyd, 2004). Unfortunately, there are some limitations, namely the redefinition of MSY for the model (5) and in a consequence finding an optimal harvest cannot be done by classical approaches (Bousquet et al, 2008) and numerical solution for stochastic control problems is highly complicated even for linear SDEs.…”
Section: F T X T U T E C T X T E P T U T C T X T U Tmentioning
confidence: 99%